Parieto‐frontal network in humans studied by cortico‐cortical evoked potential - Matsumoto, Riki (Hum Brain Mapp, 2011)
Parieto‐frontal network is essential for sensorimotor integration in various complex behaviors, and its disruption is associated with pathophysiology of apraxia and visuo‐spatial disorders. Despite advances in knowledge regarding specialized cortical areas for various sensorimotor transformations, little is known about the underlying cortico‐cortical connectivity in humans. We investigated inter‐areal connections of the lateral parieto‐frontal network in vivo by means of cortico‐cortical evoked potentials (CCEPs). Six patients with epilepsy and one with brain tumor were studied. With the use of subdural electrodes implanted for presurgical evaluation, network configuration was investigated by tracking the connections from the parietal stimulus site to the frontal site where the maximum CCEP was recorded. It was characterized by (i) a near‐to‐near and distant‐to‐distant, mirror symmetric configuration across the central sulcus, (ii) preserved dorso‐ventral organization (the inferior parietal lobule to the ventral premotor area and the superior parietal lobule to the dorsal premotor area), and (iii) projections to more than one frontal cortical sites in 56% of explored connections. These findings were also confirmed by the standardized parieto‐frontal CCEP connectivity map constructed in reference to the Jülich cytoarchitectonic atlas in the MNI standard space. The present CCEP study provided an anatomical blueprint underlying the lateral parieto‐frontal network and demonstrated a connectivity pattern similar to non‐human primates in the newly developed inferior parietal lobule in humans. Hum Brain Mapp, 2012. © 2011 Wiley Periodicals, Inc.